AB0850 CUTANEOUS LUPUS ERYTHEMATOSUS DISEASE AREA & SEVERITY INDEX (CLASI) DEMONSTRATES THRESHOLDS FOR DETECTION OF TREATMENT RESPONSE IN A PHASE 2, PLACEBO-CONTROLLED TRIAL OF USTEKINUMAB IN SLE. (2nd June 2020) - Werth, V.; Hahn, B. H.; Tsokos, G.; Rose, S.; Fei, K.; Gregan, Y. I.; Gordon, R.; Lo, K. H.; Vollenhoven, R. V.
Abstract : Background: In a Phase 2 study, Ustekinumab (UST) showed improvement at week (wk) 24 in the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) response (≥4-point improvement from baseline [BL]) vs placebo (PBO). 1 Post hoc analysis revealed that more patients (pts) on UST vs PBO achieved ≥50% improvement in total CLASI activity score. Objectives: To examine the relationships of CLASI activity responses to SLEDAI-2K (S2K) mucocutaneous disease responses. Methods: Adults with SLE (S2K ≥6, ≥1 BILAG A and/or ≥2 BILAG B scores) despite standard of care (SOC) therapy were enrolled. Pts (n=102) were randomized (3:2) to UST 6 mg/kg IV or PBO at wk 0, followed by UST 90 mg SC or PBO every 8 wks beginning at wk 8 + SOC. S2K index measures complete improvement from BL; S2K Responder Index-50 (S2K RI-50) evaluates partial improvement (≥50%) in S2K rash. CLASI rash: sum of erythema and scale/hypertrophy score. In post hoc analysis, improvement in CLASI activity score at wk 24 was calculated using increasing thresholds of BL disease activity and various cut points of improvement to define treatment response. Results: Complete improvement from BL in rash was concordant between CLASI and S2K (correlation coefficients [r] ≥0.997, Table 1 ). There was less agreement between CLASI and S2K RI-50 for assessing partial improvement in rash. Treatment difference (UST vs PBO) in % pts achieving partial improvement in rash was observed for CLASI (60% vs 38.5%), but not S2K RI-50 (51.1% vs 50%). Complete improvement from BL in mucosal ulceration was congruent between CLASI and S2K (r=1). Both instruments demonstrated greater proportions of responders to UST vs PBO. Treatment differences between UST and PBO in achieving ≥20%, ≥35%, and ≥50% improvement from BL in total CLASI activity score were noteworthy at various thresholds of disease activity (Table 2 ). Conclusion: CLASI demonstrated partial improvement in active mucocutaneous disease that was not captured by S2K RI-50. Treatment effect favoring UST vs PBO was observed across range of thresholds of BL CLASI activity and cut points used to define improvement, which have previously been shown to be clinically meaningful. 2 Findings are based on a limited sample size and treatment duration; results will be confirmed in an ongoing Phase 3 UST trial (NCT03517722 ). References: [1]Van Vollenhoven R. Lancet . 2018;392:1330 [2]Chakka S. JID. 2019;139: S101 (#587) Disclosure of Interests: Victoria Werth Grant/research support from: Biogen, Celgene, Gilead, Janssen, Viela, Consultant of: Biogen, Gilead, Janssen, Abbvie, GSK, Resolve, AstraZeneca, Amgen, Eli Lilly, EMD Serono, BMS, Viela, Kyowa Kirin, Bevra H. Hahn Grant/research support from: Janssen Research & Development, LLC, George Tsokos Grant/research support from: Janssen Research & Development, LLC, Shawn Rose Employee of: Janssen Research & Development, LLC, Kaiyin Fei Employee of: Janssen Research & Development, LLC, Y Irene Gregan Employee of: Janssen Research & Development, LLC, Robert Gordon Employee of: Janssen Research & Development, LLC, Kim Hung Lo Employee of: Janssen Research & Development, LLC, Ronald van Vollenhoven Grant/research support from: AbbVie, Amgen, Arthrogen, Bristol-Myers Squibb, GlaxoSmithKline (GSK), Janssen Research & Development, LLC, Lilly, Pfizer, Roche, and UCB, Consultant of: AbbVie, AstraZeneca, Biotest, Bristol-Myers Squibb, Celgene, Crescendo Bioscience, GSK, Janssen, Lilly, Medac, Merck, Novartis, Pfizer, Roche, UCB and Vertex, Speakers bureau: AbbVie, AstraZeneca, Biotest, Bristol-Myers Squibb, Celgene, Crescendo Bioscience, GlaxoSmithKline, Janssen, Lilly, Merck, Novartis, Pfizer, Roche, UCB, Vertex